Optimal PID Control System for Room Temperature Regulation with Classical and Hybrid Gain Scheduling Tuning Methods - Ghazali, Anith Khairunnisa; Ab Aziz, Nor Azlina; Bhuvaneswari, Thangavel; Chitra, Venugopal (International Journal of Integrated Engineering, 2025)
Indoor thermal comfort is a crucial factor for ensuring the well-being of occupants at a facility. In Malaysia's tropical climate, room temperature varies from 27°C to 37°C. Devices such as fans and air conditioning systems are frequently employed to ensure optimal thermal comfort. This study employs Proportional-Integral-Derivative (PID) technology to achieve optimal air conditioning control for maintaining a suitable room temperature. The PID is calibrated utilising three conventional tuning methods: manual tuning (MT), Ziegler-Nichols (ZN), and Cohen-Coon (CC), together with a hybrid gain scheduling approach (HGSPID). The control parameters are modified dynamically according to fluctuating environmental conditions and occupancy patterns. Three ideal room 17°C, 20°C, and 22°C are used to test the controllers. The results show that HDSPID has the best performance than the PID controller tuned using classical methods when both settling time and overshoots are considered. The CC tuning provides 0% overshoot for all tested temperatures, but the settling time is longer, while ZN has the same settling time as HGSPID but a high overshoot. MT has the worst performance in both overshoot and settling time.